Ответ(ы) на вопрос:
[latex] \frac{3x-1}{6} - \frac{x}{3} = \frac{5-x}{9} [/latex]
Приведем к общему знаменателю:
[latex]\frac{3*(3x-1)}{3*6} - \frac{6*x}{6*3} = \frac{2*(5-x)}{2*9}[/latex]
Избавимся от знаменателя ( умножим на 18):
3(3х-1) - 6х = 2 *(5-х)
9х-3-6х=10-2х
3х-3=10-2х
3х+2х=10+3
х=13/5 =2,6
Проверим:
[latex]\frac{3*2,6-1}{6} - \frac{2,6}{3} = \frac{5-2,6}{9} \\ \\ \frac{6,8}{6} - \frac{2,6}{3} = \frac{2,4}{9} \\ \\ [/latex]
[latex]\frac{20,4 -15,6}{18} = \frac{4,8}{18} \\ \\ \frac{4,8}{18} = \frac{4,8}{18} [/latex]
Не нашли ответ?
Похожие вопросы